Comparison of outcome of patients with CLL who are referred or nonreferred to a specialized CLL clinic: a Canadian population‐based study. (18th February 2016) - Beiggi, Sara; Banerji, Versha; Deneka, Angela; Griffith, Jane; Gibson, Spencer B.; Johnston, James B.
Abstract: Chronic lymphocytic leukemia and small lymphocytic lymphoma (CLL/SLL) patients in Manitoba are either referred to the CLL Clinic at CancerCare Manitoba (CCMB) or are followed by other hematologists and general practitioners. However, it has been unclear whether referral to the CLL clinic influences patient outcome. Overall survival (OS) was assessed for all CLL/SLL patients diagnosed in Manitoba between 2007 and 2011. Of 555 patients, 281 (51%) were referred to the CLL clinic. Patients seen in this clinic had a twofold increased OS compared to patients who were managed by other hematologists and general practitioners (HR 2.375, P 0.0002) when adjusted for age, gender, presence of pre‐ or post‐CLL cancer, treatment and urban/rural location. In the nonreferred population there was a striking correlation between advancing age and decreasing OS. However, this correlation was almost eliminated in the referred population who were more likely to receive chemotherapy. Patients referred and seen in the CLL clinic have an improved OS compared to nonreferred patients and this appears to be primarily related to improved OS in the elderly. Possible explanations for this finding are discussed. Abstract : Chronic lymphocytic leukemia and small lymphocytic lymphoma (CLL/SLL) patients in Manitoba are either referred to the CLL Clinic at CancerCare Manitoba or are followed by other hematologists and general practitioners. Patients seen in the CLL clinic have an improved overall survival (OS) compared to nonreferred patients and this appears to be primarily related to improved OS in the elderly.